Um Afrodisíaco Potencialmente Fatal: Intoxicação por Cantaridina - Diaz, P (2020)
Cantharidin is a toxin extracted from coleoptera beetles, commonly known as 'Spanish fly'. Traditionally it was used as an aphrodisiac, a vesicant or as an abortifacient. Intoxication by this substance has been widely reported, generally associated with gastrointestinal complications, such as digestive hemorrhage, and genitourinary disorders, such as hematuria and acute kidney injury. The authors describe the case of a 51-year old male patient who developed severe cantharidin poisoning after ingesting a preparation ('tea formulation') containing the substance. The patient reported a burning sensation in his oral cavity, diarrhea and hematuria, having sustained acute kidney injury and atypical neurological symptoms. Due to the lack of an antidote, the available treatment options are reduced to supportive measures. This case strengthens the need for a thorough medical history to ascertain the use of 'natural' products and medicinal herbs (i.e. of unregulated origin), and the importance of educating the community to their potential toxicity.